2011
DOI: 10.1371/journal.pone.0021932
|View full text |Cite|
|
Sign up to set email alerts
|

Should Metabolic Diseases Be Systematically Screened in Nonsyndromic Autism Spectrum Disorders?

Abstract: BackgroundIn the investigation of autism spectrum disorders (ASD), a genetic cause is found in approximately 10–20%. Among these cases, the prevalence of the rare inherited metabolic disorders (IMD) is unknown and poorly evaluated. An IMD responsible for ASD is usually identified by the associated clinical phenotype such as dysmorphic features, ataxia, microcephaly, epilepsy, and severe intellectual disability (ID). In rare cases, however, ASD may be considered as nonsyndromic at the onset of a related IMD.Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 42 publications
2
26
0
3
Order By: Relevance
“…In these disorders, however, the clinical picture incorporates additional signs such as severe behavioral disorders, cognitive regression, and ocular, liver, or other neurological signs over time. In a retrospective study of 274 nonsyndromic ASD patients, we showed, as already stated by others [63] that the diagnostic yield of such a workup was very low [64].…”
Section: Inborn Errors Of Metabolism As a Cause Of Autism Spectrum DIsupporting
confidence: 58%
“…In these disorders, however, the clinical picture incorporates additional signs such as severe behavioral disorders, cognitive regression, and ocular, liver, or other neurological signs over time. In a retrospective study of 274 nonsyndromic ASD patients, we showed, as already stated by others [63] that the diagnostic yield of such a workup was very low [64].…”
Section: Inborn Errors Of Metabolism As a Cause Of Autism Spectrum DIsupporting
confidence: 58%
“…Despite speculation that creatine deficiency is common in children with ASD, our findings suggest that inborn errors of creatine synthesis (AGAT-D and GAMT-D) and creatine transport (CrT-D) are unlikely to play a role in the pathogenesis of ASD in many children. Two previous investigations into the prevalence of CDS in patients with ASD had similar findings: urine of 203 children with nonsyndromic ASD found none of the children being affected with CDS 28 ; screening of 100 boys with ASD for a mutation in the SLC6A8 gene (CrT defect, X-linked) revealed 1 male patient with a novel gene variant falsely reported as "affected." 27 Of note, this patient had a normal urine creatine/creatinine ratio and normal creatine uptake studies in fibroblasts, thus excluding CrT-D. 37 The same gene variant c.1162G>A was identified in 1 boy in our study and considered as nondisease-causing single nucleotide polymorphism.…”
Section: Discussionmentioning
confidence: 67%
“…24 Data using human fetal striatal and mesencephalic tissue identified creatine as a potent natural survival and neuroprotective factor for γ-aminobutyric acid-ergic neurons in a model for Huntington disease 25 and of dopaminergic neurons in a model for Parkinson disease. 26 Recent interest in routine screening children with ASD for inborn errors of metabolism, and in particular CDS, 27,28 raises the question of how many children with ASD could potentially benefit from such screening. The purpose of the current study is to establish the prevalence of CDS in children with ASD, using a rational approach of biochemical and genetic testing for creatine metabolism.…”
Section: What This Study Addsmentioning
confidence: 99%
“…However, in a retrospective study of 274 nonsyndromic patients with ASD, we have shown (as already stated by others) that the diagnostic yield of such a work-up was very low. 6 Of note, in the two reports the clinical picture was quite specific. First, the patients were from consanguineous families.…”
mentioning
confidence: 89%